Compensation for victims of sexual offences through criminal justice in Tanzania: a case for a human rights-based approach - Bakta, Seraphina; Mapendo, Deogratias (African Journal of Law and Justice System, 2024)
A research paper submitted to the African Journal of Law and Justice System Vol. 1, No. 2 (2022)